2014
DOI: 10.1099/mic.0.073783-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the six chromate ion transporter homologues of Burkholderia xenovorans LB400

Abstract: The chromate ion transporter (CHR) superfamily comprises transporters that confer chromate resistance by extruding toxic chromate ions from cytoplasm. Burkholderia xenovorans strain LB400 has been reported to encode six CHR homologues in its multireplicon genome. We found that strain LB400 displays chromate-inducible resistance to chromate. Susceptibility tests of Escherichia coli strains transformed with cloned B. xenovorans chr genes indicated that the six genes confer chromate resistance, although under dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Strikingly, expression of chrA SO in E . coli makes the strain capable of growing in the presence of high chromate concentrations, as also observed for the plasmid-encoded ChrA of Shewanella ANA-3 and for several ChrA of Burkholderia xenovorans LB400 [ 34 , 35 ]. Therefore ChrA SO most probably functions as a chromate efflux pump and expulses chromate ions from the cytoplasm, as demonstrated for some members of the CHR family [ 13 , 34 ].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Strikingly, expression of chrA SO in E . coli makes the strain capable of growing in the presence of high chromate concentrations, as also observed for the plasmid-encoded ChrA of Shewanella ANA-3 and for several ChrA of Burkholderia xenovorans LB400 [ 34 , 35 ]. Therefore ChrA SO most probably functions as a chromate efflux pump and expulses chromate ions from the cytoplasm, as demonstrated for some members of the CHR family [ 13 , 34 ].…”
Section: Discussionmentioning
confidence: 85%
“…In B . xenovorans LB400, which possesses six genes encoding chromate ion transporters, only the chrA2 gene present on a megaplasmid is subject to chromate-induced expression [ 35 ]. Interestingly, it was recently demonstrated that ChrA2 is the major determinant of chromate resistance in this organism [ 37 ].…”
Section: Discussionmentioning
confidence: 99%